Profile of glaucoma in a major eye hospital in North India - Das Jayachandra (Indian Journal of Ophthalmology, 2001)
Purpose: To study the clinical profile and distribution of various subtypes of glaucoma in a referral practice in North India. Method: A retrospective analysis was done of 2425 patients who attended the glaucoma clinic in a tertiary eye-care centre for five years from Januaryl995 to December 1999. A detailed history was obtained and a thorough examination was performed, including gonioscopy, disc assessment, applanation tonometry and automated perimetry. Diurnal variation of IOP and provocative tests for glaucoma were done where applicable. Result: Primary angle closure glaucoma (PACG) was the most common glaucoma subtype. The primary open angle glaucoma (POAG) to the PACG ratio was 37:63. Chronic angle closure glaucoma (CACG) was the most common PACG subtype. The majority of CACG cases were relatively asymptomatic. Male dominance was seen for POAG, juvenile open angle glaucoma (JOAG), CACG, normal tension glaucoma (NTG) and secondary glaucomas. Female dominance was seen for ocular hypertension (OHT), acute or intermittent ACG and developmental glaucomas. The mean age in years at presentation was POAG: 60.54 years (males 61.54 years, females 59.01 years) and PACG: 55.13 years (males 57.25 years, females 53.60). The three common secondary glaucomas were: glaucoma secondary to adherent leucoma, aphakic and pseudophakic glaucomas and traumatic glaucomas. Advanced glaucoma was detected in 42 to 53% of patients and bilateral blindness in 8 to 14% of patients in various subtypes. Conclusion: Compared to Caucasians, glaucoma patients in North India seem to present nearly a decade earlier and the disease is more advanced at presentation. While PACG is the most commonly encountered glaucoma, NTG and exfoliative glaucoma are relatively rare.